Testing the Best Development Planning Collaboration Model in Moderating the Acceleration of Regional Economic Development - Panjaitan, Dikky Anugerah; Lubis, Satia Negara; Sabrina, T.; Badaruddin, Badaruddin (International Conference on Sciences Development and Technology, 2023)
Regional economic development is the ability to generate additional income or improve welfare. The effectiveness of the Sumatra Provincial Government in implementing economic development. This research aims to examine a collaborative development planning model that can support economic development in North Sumatra Province. Structural Equation Model (SEM) was adopted as an analytical framework using a quantitative approach with a focus on cause-and-effect relationships and influences. The results show that only the Top-Down Planning Pattern has a direct impact on Regional Economic Development. Apart from that, the collaborative model of Dawes & Eglene, Djumara, and Ansell & Gash can increase regional economic development. Based on data analysis, the Collaborative model is proven to be effective compared to the direct influence of Bottom-Up and Top-Down planning. Meanwhile, Bottom-Up planning which is strengthened by the Djumara model was chosen as the most effective in increasing regional economic development. Among the three collaboration models, Djumara and Ansell & Gash have a positive impact on this variable. However, through indirect testing, Dawes & Eglene, Djumara, and Ansell & Gash can mediate or improve these variables. Based on the results, Bottom-Up planning through the Djumara model is most effective in increasing regional economic development. This model is recommended as a shortcut to effective development planning using Collaborative Culture, Leadership, Strategy, and Team Processes.